The Influence of the Level of Popularity of Influencer, the Preference of Message Disclosure, and the Consumer Skepticism of Advertising on the Purchase Intention of Somethinc - Kanaya Az Zahrah; Tandiyo Pradekso; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Somethinc uses various influencers with different levels of popularity namely mega, macro, micro, and nano to promote their products. The existence of influencers makes a lot of sponsored content spread on Instagram. However, this has many pros and cons because a lot of content does not use the “Paid Partnership with” feature. This kind of advertising model can also make consumers become defensive and lead to skepticism because there is no transparency about the persuasive nature of the content that influencers share. From late 2020 to early 2021, several national surveys showed that Somethinc was not consumers’ first choice when buying beauty products. The theory used in this study is the Source of Attractiveness Model and the Persuasion Knowledge Model, with the sampling technique of non-probability sampling. The sample consists of 100 people with female characteristics, aged 18-35, who have seen sponsored content by Somethinc’s influencers. The results of the first hypothesis test using a simple regression technique show that there is no influence on the level of popularity of influencers on purchase intention of Somethinc with a significance value of (0.931). The results of the second hypothesis test using multiple regression techniques show that there is no influence on the preference of message disclosure and the consumer skepticism of Advertising on Somethinc's purchase intention with a significance value (0.098).